Perbandingan LK CHANNEL Dengan Literacy News Dalam Mengemas Informasi Melalui Via YOUTUBE - Alfian; Al Akbar; Nurul; Ayu; Jumriani; hajra, Hajrah (Communication and Islamic Broadcasting Studies IAIN Parepare, 2023)
The development of technology is currently increasing in the social life of society, marked by the increasingly widespread use of the internet and mobile phones which make it easier for people to receive information. One of the most popular is Youtube. Youtube itself has many benefits, including searching for movies, watching music, the latest videos and much more that can be watched on Youtube.Youtube as an alternative media for public entertainment is able to position itself so important that its existence can be categorized as a source of income by some groups of people.As a study program that is close to communication media, the Islamic Communication and Broadcasting and Islamic Journalism study programs use YouTube as a means to disseminate information to IAIN Parepare students. The name of the Youtube channel created by the Islamic Communication and Broadcasting Study Program is LK Channel and for the Islamic Journalism Study Program is Literacy News.It is hoped that the LK Channel and Literacy News will become one of the learning media for KPI and Islamic Journalism Study Program students to be more productive in producing various videos such as news shows about the IAIN Parepare campus or inspirational, educational and entertaining videos.